2021
DOI: 10.3390/ijms22126199
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Tumor Suppressive Genes Regulated by miR-31-5p and miR-31-3p in Head and Neck Squamous Cell Carcinoma

Abstract: We identified the microRNA (miRNA) expression signature of head and neck squamous cell carcinoma (HNSCC) tissues by RNA sequencing, in which 168 miRNAs were significantly upregulated, including both strands of the miR-31 duplex (miR-31-5p and miR-31-3p). The aims of this study were to identify networks of tumor suppressor genes regulated by miR-31-5p and miR-31-3p in HNSCC cells. Our functional assays showed that inhibition of miR-31-5p and miR-31-3p attenuated cancer cell malignant phenotypes (cell proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…Upregulation of miR-31-5p has been observed in HNSCC cancers and has been confirmed by The Cancer Genome Atlas (TCGA) data analysis [63]. Functional assays have shown that miR-31-5p is an oncogenic miRNA in HNSCC [64].…”
Section: Mir-31-5pmentioning
confidence: 74%
“…Upregulation of miR-31-5p has been observed in HNSCC cancers and has been confirmed by The Cancer Genome Atlas (TCGA) data analysis [63]. Functional assays have shown that miR-31-5p is an oncogenic miRNA in HNSCC [64].…”
Section: Mir-31-5pmentioning
confidence: 74%
“…Tumor-suppressive miRNAs are frequently downregulated, whereas their oncogene targets are upregulated, in cancer cells. A previous analysis of our RNA-sequencing-based miRNA signature of OSCC revealed that miR-125b-5p and miR-140-5p were downregulated in cancer tissues [ 42 ]. Our present study showed that these miRNAs have tumor-suppressive roles, and miR-125b-5p and miR-140-5p directly regulate the expression of CORO2A in OSCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…RNA was extracted from cell lines and subjected to this study as described previously [ 42 , 57 , 58 ]. The TaqMan probes and primers used in this study are listed in Table S4 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations